Evaporation-induced formation of fractal-like structures from nanofluids - Crivoi, Alexandru (2013)
After the nanofluids are fully dried, the self-assembled nanoparticles can form various structures on the substrate. The fractal-like patterns are among them. The two-dimensional Kinetic Monte Carlo model is developed to predict the drying patterns of the nanofluids in an open domain, where the dewetting front shrinks from the edge toward the center. The simulation reveals that the initially dispersed particles can be deposited into an isotropic branched structure which remains frozen after full evaporation of the base fluid. The well-developed fractal-like particle aggregates are different from the fractal cavities obtained in the previous closed domain simulation. The present prediction of the fractal particle aggregation is verified by the experiments with the water-based nanofluids. The images taken using a scanning electron microscope prove that the evaporation-induced branched microstructures are formed by the nanoparticles as the water is totally dried.